Penerapan Latihan Memantulkan Bola ke Dinding dalam Meningkatkan Kemampuan Passing Bawah Permainan Bola Voli pada Siswa Sekolah Dasar - Ayi Rahmat; Mukhtar Ridwan; Dedi Aryadi; Ira Arini (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
The background of this research is the lack of ability to pass under volleyball as a starting movement for elementary school students in introducing volleyball. For this reason, this study aims to be able to improve the ability to pass under volleyball by applying exercises to bounce the ball off the wall. The research method used is a quantitative experimental research method with a one group pretest-posttest research design. The population in this study were all elementary school students in Rangkasbitung District and the sample in this study were students who took volleyball extracurricular activities. The instrument used was a test instrument carried out in 16 meetings twice for pretest and posttest. Data analysis techniques using instrument validity tests, analysis prerequisite tests and hypothesis testing. The results showed that testing the hypothesis using the t-test, the results obtained were tcount of 15.3 while the value of ttable with a significance level of 0.05 was 2.26. From the results of testing the hypothesis it is known that tcount>ttable (15.3> 2.26), so it can be concluded that H0 is rejected and H1 is accepted. This shows that the application of bouncing the ball off the wall exercise has a positive influence on the ability to pass under volleyball in extracurricular students. Based on the results of the study, the results of the posttest bouncing the ball off the wall were higher than the pretest. This is comparable to the score of the lower passing ability, these results indicate that the learning outcomes which are psychomotor abilities play a very important role in the lower passing ability.